2012
DOI: 10.1016/j.bjid.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B among pregnant women assisted at the public maternity hospitals of São Luís, Maranhão, Brazil

Abstract: The prevalence of HBsAg in pregnant women in this study confirmed that São Luís is a low endemicity area. Occult hepatitis B was not detected in these samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 18 publications
5
18
1
5
Order By: Relevance
“…Confirming this trend, absence or low prevalence of OHB has been the most commonly obtained result in Brazilian studies on different populations, ranging from 0% to 2.7% …”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Confirming this trend, absence or low prevalence of OHB has been the most commonly obtained result in Brazilian studies on different populations, ranging from 0% to 2.7% …”
Section: Discussionsupporting
confidence: 62%
“…Confirming this trend, absence or low prevalence of OHB has been the most commonly obtained result in Brazilian studies on different populations, ranging from 0% to 2.7%. [41][42][43][44][45] In this study, the prevalence of OHB in CRF patients on dialysis was not correlated with gender, age, previous renal transplantation, serological profile for HBV, or the time the patient was on hemodialysis. The only correlation found was related to anti-HCV positivity.…”
Section: Discussionmentioning
confidence: 49%
“…However, there are few studies on the screening of the disease in the gestational period in Brazil, especially in the state of Rio de Janeiro. Souza et al reported a prevalence of chronic HBV among Brazilian pregnant women ranging from 0.5% to 8.7%, depending on the region studied (5) .…”
Section: Discussionmentioning
confidence: 99%
“…The most recent results indicated a reduced prevalence of hepatitis B throughout the country, classifying Brazil as being of low endemicity. Most studies showed a prevalence of HBV inferior to 1% (3)(4)(5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%
“…But HBV infection prevalence among pregnant women living in Nigeria, Uganda, Ethiopia, Mauritania, Mali, Yemen and South Africa was much higher than the prevalence among Iranian pregnant women. In addition, Pakistani, Libyan and Turkish pregnant women were slightly more infected than Iranian women (4,7,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). Higher infection rates in most African countries and lower rates among women in most European countries indicates the effect of health promotion and vaccine coverage on the patterns of infection.…”
Section: Discussionmentioning
confidence: 99%